2018
DOI: 10.1016/j.ajur.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of adjunct caudal block on postoperative analgesia in robot-assisted laparoscopic radical prostatectomy: A prospective randomized controlled, single blinded pilot study in a tertiary centre

Abstract: ObjectiveCaudal block provides satisfactory postoperative pain relief in lower abdominal operations. This pilot study explores its safety and effect on postoperative pain control in patients who underwent robot-assisted laparoscopic radical prostatectomy (RARP).MethodsFrom 2013 to 2014, 40 consecutive patients were randomized into two groups — one received caudal block using ropivacaine immediately after operation, the other received standard analgesia. Primary outcome measure was pain score based on 11-point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Enhanced recovery after surgery has become an important focus of perioperative management in many types of surgeries, including general surgery [ 19 ], orthopedics [ 20 ], and gynecologic oncological surgery [ 21 ]. Cystectomy is the most common enhanced recovery after surgery pathway performed in urology, due to a reduction in the rate of complications and the length of stay [ [22] , [23] , [24] ]. However, reported data about the development of ambulatory surgery programs in urologic diseases are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced recovery after surgery has become an important focus of perioperative management in many types of surgeries, including general surgery [ 19 ], orthopedics [ 20 ], and gynecologic oncological surgery [ 21 ]. Cystectomy is the most common enhanced recovery after surgery pathway performed in urology, due to a reduction in the rate of complications and the length of stay [ [22] , [23] , [24] ]. However, reported data about the development of ambulatory surgery programs in urologic diseases are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, various bupivacaine supplements have been used in many paediatric surgeries to increase the duration and quality of pain relief. Addition of tramadol to bupivacaine resulted in a dose-dependent upsurge in analgesia postoperatively [16][17] . This study showed a clinically and statistically substantial period of postoperatively pain reduction.…”
Section: Discussionmentioning
confidence: 99%
“…We do not recommend epidural analgesia despite positive studies published since January 2015 and before [10] because the technique is invasive and conveys a risk of side effects and complications such as hypotension, dural puncture and even epidural haematoma [56]. Caudal block is not recommended because only one negative study has been published on its use [26].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%